Highly Fluorescent Magnetic Nanobeads with a Remarkable Stokes Shift as Labels for Enhanced Detection in Immunoassays. Issue 20 (17th April 2018) - Salis, Francesca; Descalzo, Ana B.; Benito‐Peña, Elena; Moreno‐Bondi, María C.; Orellana, Guillermo
Abstract: Fluorescence immunoassays are popular for achieving high sensitivity, but they display limitations in biological samples due to strong absorption of light, background fluorescence from matrix components, or light scattering by the biomacromolecules. A powerful strategy to overcome these problems is introduced here by using fluorescent magnetic nanobeads doped with two boron‐dipyrromethane dyes displaying intense emission in the visible and near‐infrared regions, respectively. Careful matching of the emission and absorption features of the dopants leads to a virtual Stokes shift larger than 150 nm achieved by an intraparticle Förster resonance energy transfer (FRET) process between the donor and the acceptor dyes. Additionally, the magnetic properties of the fluorescent beads allow preconcentration of the sample. To illustrate the usefulness of this approach to increase the sensitivity of fluorescence immunoassays, the novel nanoparticles are employed as labels for quantification of the widely used Tacrolimus (FK506) immunosuppressive drug. The FRET‐based competitive inhibition immunoassay yields a limit of detection (LOD) of 0.08 ng mL −1, with a dynamic range (DR) of 0.15–2.0 ng mL −1, compared to a LOD of 2.7 ng mL −1 and a DR between 4.1 and 130 ng mL −1 for the immunoassay carried out with direct excitation of the acceptor dye. Abstract : Brilliant magnetic nanoparticles with a large Stokes shift demonstrate the sensitivity improvement in fluorescence‐based immunoassays when measuring the sensitized emission (>650 nm) of a near‐infrared fluorescent boron‐dipyrromethene dye generated via intraparticle Förster resonance energy transfer (FRET). The nanobeads are tested in the detection of the immunosuppressant drug Tacrolimus by a competitive immunoassay down to 0.08 ng mL −1 .